Pengembangan E-Modul Berbasis Learning Cycle 5E untuk Meningkatkan Kemampuan Berpikir Kreatif Siswa SMP - Meri Kartikasari; Ismet Ismet; Ida Sriyanti (Jurnal Penelitian Pendidikan IPA, 2023)
A valid, practical, and effective learning cycle 5e-based e-module has been successfully developed. The method used is Development Research with the Rowntree development model which consists of three stages, namely the planning stage, the development stage, and the evaluation stage. The instruments used in this research are validity, practicality and effectiveness test instruments.Â  The development process through content validity test, language, suitability of learning cycle 5E and creative thinking ability, practicality test, and field test. The results showed that the e-module developed had an average validity percentage of 4.03 with a good category. In the practically test, the e-module averaged 4.6 with a very practical category. The test of the effectiveness of the use of e-modules has an average n-gain of 0.7 with a high category of improving students' creative thinking skills.